(untitled) (Salud, Arte y Cuidado, 2026)
Since the last century, women artists have recognized, through their creative sensitivity, women’s capacity to awaken the most secret forces hidden within human beings through a conscious and sacred motherhood that can significantly impact the future of humanity and the changes that will transform society. In this article, we will explore these hidden powers within women and how, through their thoughts and will, they can create ideal characters in their children during pregnancy, thus manifesting an ideal related to the advent of a fraternal society. Women artists are already feeling the need to elevate themselves and form a collective unity, fighting for recognition of their exceptional capacity as trainers and educators in the true nature of things, where gestation plays an enormous role